Some issues of using maternity (family) capital for the purchase of housing - F.N. Bagautdinov; A.D. Iskhakov (Ученые записки Казанского университета: Серия Гуманитарные науки)
This article considers certain problems in the implementation of the provisions of the Federal Law “On additional measures of state support for families with children” regarding the use of maternity (family) capital for the purchase of housing, as well as the capacity of prosecutors to respond efficiently to violations identified in this activity. One of the violations while implementing the national project “Demography” is the failure of parents to register their underage children’s right of ownership to the housing in case maternity capital is used to purchase this housing. Possible ways to evade the allocation of a share in the housing by parents to their underage children and the prosecutor’s role in solving this problem were analyzed. To encourage parents to timely allocate a share in the housing to their children, it was suggested to introduce administrative responsibility for violating the six-month term of compulsory registration of shares in such cases. The problem of allocation of a share to children when unfinished construction projects and residential premises are purchased with the use of maternity capital and mortgage loans was also discussed. The procedure of how and, most importantly, in what way shares should be allocated to children was explored: there are no residential premises, it is unknown when the house will be completed (and whether it will be completed at all) as the terms for individual housing construction are not established. Therefore, it was suggested that changes must be made to the Federal Law “On mortgages”.